Who Serves the Poor? : Surveying Civil Servants in the Developing World - Rogger, Daniel (World Bank, Washington, DC, 2017)
Who are the civil servants that serve poor people in the developing world? This paper uses direct surveys of civil servants -- the professional body of administrators who manage government policy -- and their organizations from Ethiopia, Ghana, Indonesia, Nigeria, Pakistan and the Philippines, to highlight key aspects of their characteristics and experience of civil service life. Civil servants in the developing world face myriad challenges to serving the world's poor, from limited facilities to significant political interference in their work. There are a number of commonalities across service environments, and the paper summarizes these in a series of 'stylized facts' of the civil service in the developing world. At the same time, the particular challenges faced by a public official vary substantially across and within countries and regions. For example, measured management practices differ widely across local governments of a single state in Nigeria. Surveys of civil servants allow us to document these differences, build better models of the public sector, and make more informed policy choices.